1994
DOI: 10.1161/01.cir.90.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vasodilator reserve, pain perception, and sex in patients with syndrome X.

Abstract: When patients with syndrome X are compared with control subjects, no differences are found in MBF either at rest or after dipyridamole, despite syndrome X patients experiencing chest pain after dipyridamole to the same extent as patients with CAD. These findings, together with the absence of any relation among MBF, chest pain, and ECG changes under stress, cast further doubt on ischemia as the basis of the chest pain, at least in the majority of syndrome X patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(57 citation statements)
references
References 52 publications
1
54
0
2
Order By: Relevance
“…Syndrome X is more common in women than in men (679,916 -918). Chest pain can vary from that of typical angina pectoris to chest pain with atypical features to chest pain that simulates UA secondary to CAD (917). Other atypical features can be prolonged chest pain at rest and chest pain that is unresponsive to NTG (919).…”
Section: Definition and Clinical Picturementioning
confidence: 99%
“…Syndrome X is more common in women than in men (679,916 -918). Chest pain can vary from that of typical angina pectoris to chest pain with atypical features to chest pain that simulates UA secondary to CAD (917). Other atypical features can be prolonged chest pain at rest and chest pain that is unresponsive to NTG (919).…”
Section: Definition and Clinical Picturementioning
confidence: 99%
“…9,32 Although the CMR perfusion sequence we used resulted in greatly improved spatial resolution (2.6 versus Ϸ8.4 mm with PET), transmural hypoperfusion was not evidenced. Previous PET studies reported a wide dispersion of MBF values after dipyridamole stress in patients with syndrome X.…”
Section: Karamitsos Et Almentioning
confidence: 99%
“…[5][6][7] Moreover, the observation that patients with syndrome X commonly experience their typical chest pain during cardiac catheterization maneuvers (simple catheter movements or saline injection in the heart) has led several investigators to believe that enhanced cardiac pain perception is a central component of the pathophysiology of the syndrome. 8,9 microspheres for the assessment of blood flow, 12 and we have previously used this technique to report resting myocardial blood flow (MBF) in patients with hibernating myocardium. 13 Over the past decade, several investigators have reported on CMR perfusion in cardiac syndrome X with conflicting results.…”
mentioning
confidence: 99%
“…The regions of interest were superimposed onto the kinetic time frames recorded during the C 15 O 2 inhalation and washout; this produced a planeaveraged time-activity curve for each region, which, together with the arterial input function, were fitted to a single tissue compartment tracer kinetic model to give values for regional MBF (mL ⅐ min Ϫ1 ⅐ g Ϫ1 ) as previously reported. 14 In addition, whole heart MBF was determined by defining additional regions of interest, each drawn to encompass the whole of the left ventricle within each image plane. These whole heart regions were superimposed onto the kinetic time frames as described above for the subregions to provide a single whole left ventricle time-activity curve before the calculation of MBF.…”
Section: Pet Data Analysismentioning
confidence: 99%